THE RELATIONSHIP BETWEEN KNOWLEDGE OF MOTIVATION AND FAMILY SUPPORT ON DIET COMPLIANCE IN FAMILIES WITH DIABETES MELLITUS - Erlina Y Kongkoli; Nuraeni Jalil; Maryama Nur; Baharuddin Baharuddin; Sudirman Sudirman (Bajang Institute, 2022)
Diabetes mellitus has become a common health problem that can be found everywhere, the number of people with diabetes mellitus is increasing continuously. Even diabetes mellitus will tend to have a frightening effect when considering some complication caused by the eyes, heart, kidneys, nerves, or the possibility of amputation can occur as well. Diabetes mellitus is a world health problem because the prevalence and cases of this disease continue to increase, both in industrialized countries including Indonesia. WHO (Wordl Health Organization, 2018) explains the diagnostic criteria for diabetes mellitus (DM), namely if fasting blood glucose levels are > 126 mg/dl or random blood glucose > 200 mg/dl. The pancreas regulates glucose levels in the release of glucagon, glucagon is an insulin antagonist which has a role in increasing blood sugar levels and then accelerating the rate of release from the liver. Insulin also stimulates glucose into glycine (a form of glucose conversion to become energy reserves) and stores it in the cells. Purpose: to analyze the relationship between knowledge of motivation and family support for dietary compliance in families with diabetes mellitus. Method: the literature study used is where the collection is done through the database google scholar, research gate, and garuda portal. which the collection was carried out trought the database google scholar, research gate, and garuda portal. Research Results: from the total sample that was used for review from ten journals, there were 685 respondents who were given family support in dietary compliance. Most of the respondents who received family support could improve their dietary compliance. Conclusion: the results obtained from a review of ten journals showed that there was a significant relationship between knowledge of motivation and family support for dietary compliance so that it could improve dietary compliance by people with diabetes mellitus.